Contrasted crustal sources for peraluminous granites of the segmented Montes de Toledo Batholith (Iberian Variscan Belt) - Villaseca,C.; Perez-Soba,C.; Merino,E.; Orejana,D.; Lopez-Garcia,J.A.; Billstrom,K. (Journal of Geosciences, 2008)
The Variscan Montes de Toledo Batholith (MTB) is an E-W linear array of peraluminous granite plutons which is chemically segmented. The study is focused on the western segment of the MTB (W-MTB), mainly composed of granites with slightly lower CaO and higher P2O5 contents than associated eastern plutonic units and nearby S-type granites, giving them a more pronounced peraluminous nature. The chemical contrast is also observed in isotopic composition, especially in radiogenic Nd and Pb ratios. The W-MTB granites have higher initial εNd (-5.0 to -5.9) and lower 206Pb/204Pb and 208Pb/204Pb ratios than peraluminous types from the E-MTB segment. A mixed pelitic-greywackeous derivation from regional Neoproterozoic formations is suggested whereas lower crustal and meta-igneous sources were involved in the origin of the easternmost MTB granites. The presence of igneous muscovite together with coexisting andalusite and sillimanite in some of the studied granites suggests that solidus was reached at 650-700 °C and depth corresponding to the pressure of 2-3 kbar.
Keywords: peraluminous granites; andalusite; sillimanite; Sr-Nd-Pb isotopes; Iberian Variscan Belt